SAT0621-HPR EVALUATION OF THE SOCIAL IMPACT OF THE DISEASE IN PATIENTS WITH REUMATOID ARTHRITIS, ANQUILOSING SPONDYLITIS, AND SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Cano Garcia, L.; Mena-Vázquez, N.; Al Mashhadani, N.; Manrique Arija, S.; Ureña, I.; Fernandez-Nebro, A.
Abstract : Background: Objectives: To describe the impact of the disease on patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) or ankylosing spondylitis (EA) on the social health of people who suffer from it. Methods: Cross section of a consecutive sampling of patients with AS, RA or SLE. Selection criteria: age ≥18 years with AS (ASAS criteria), AR (EULAR / ACR 2010 criteria) and SLE (ACR-EULAR criteria) able to understand and willing to perform the questionnaires. Protocol: All patients who attended a consultation between October and December 2019 were offered to participate in the study. After their approval and verification of the inclusion criteria, they conducted a battery of PROMIS platform questionnaires focused on assessing their social health. Likewise, data on their disease, comorbidities and socio-labor profile were collected. All participants signed an informed consent and the study was approved by the CEIC of the referral hospital. Main outcomes: The variables collected by the questionnaires evaluate social health in several areas: mobility, depression, satisfaction with social relationships, social isolation, company, ability to participate in social activities, emotional support, instrumental support and support through information. Statistical analysis: Descriptive, bivariate analysis using t-student, ANOVA and χ2;, followed by multivariate linear regression (RLM) (Vd: ability to participate in continuous social activities 7-35). Results: 151 patients participated: 50 with RA (90% women, mean age 55.12 ± 13.64 years), 51 with AS (51% women, 52.59 ± 12.15 years) and 50 patients with SLE (96 % women, mean age 47.14 ± 11.3 years). The most frequent comorbidities were: arthritis, visual impairment, anxiety and depression (table 1). These results present a greater tendency to depression and anxiety patients of SLE. No significant differences were observed in most of the social questionnaires analyzed between groups (table 2), except in a worse mobility in patients with RA and AD compared to SLE (p = 0.017). About half of the patients in all groups had depression (43%) and reduced mobility (63.6%). All groups are satisfied with their social role 128 (85.3%), have the capacity to participate in social activities 140 (94%) and feel accompanied 147 (97.4%). On the contrary, the social isolation figure is 42 (28%). Social isolation implies an affectation of the serious social role in patients who claim to be accompanied, so it is not secondary to loneliness or lack of family support. In the multivariate analysis it was observed that the independent variables that were associated with the ability to participate in social activities were satisfaction with social relations (β = 0.349 [p = <0.001]), mobility (β = 0.309 [p = < 0.001]), depression (β = -0.186 [p = <0.011]) and social isolation (β = -0.195 (p = 0.001)). This model would explain 32% of the variability in the ability to participate in social activities. (R2 = 0.32). Conclusion: The predictors of the ability to participate in social activities in patients with RA, AD and SLE were: depression, mobility deficit, social isolation and satisfaction with social activities. Patients with RA, AD and SLE present similar data, so there are no differences due to pathologies in the social role, highlighting that they have a good social support and despite this there is social isolation being able to be associated with the deficit in mobility and high rates of depression. Disclosure of Interests: None declared